PERAN BADAN DAKWAH ISLAM SEBAGAI WADAH PEMBENTUKAN KARAKTER RELIGIUS SISWA SMK NEGERI 5 KOTA MALANG - Achmad Sholachuddin Anas; Azhar Haq; Adi Sudrajat (VICRATINA, 2020)
BDI is an extracurricular based on religion in vocational state high school  5 Malang city. The main purpose of BDI is building student’s religious character of vocational state high school  5 Malang city. This article is explaining the roles, obtacles and the solution of the building student’s (member) religious chararacter trough the BDI extracurricular. Researches use a qualitative appoarch to the type of case study research. The data collection thecniques use interviews, observation, and documentation. The religous character building of BDI’s member is from doctrinating and habituating, so that the member can be habitual and be contribute to surrounding environment. The obtacles of character building of BDI’s member is too much member that have problem like a broken home, and too much member that chum with another bad friend. It means, they can to be affected too. So, the solution is giving them more duty with beeing the coordinator in every activities and event of BDI. It aim to motivate them to be a more productive with the possitive thing, so that they can affect the other friend.